2017
DOI: 10.1016/j.jqsrt.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Modeling uncertainties in estimation of canopy LAI from hyperspectral remote sensing data – A Bayesian approach

Abstract: Hyperspectral remote sensing data carry information on the leaf area index (LAI) of forests, and thus in principle, LAI can be estimated based on the data by inverting a forest reflectance model. However, LAI is usually not the only unknown in a reflectance model; especially, the leaf spectral albedo and understory reflectance are also not known. If the uncertainties of these parameters are not accounted for, the inversion of a forest reflectance model can lead to biased estimates for LAI. In this paper, we st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The method is based on Bayesian inversion of a physically-based forest reflectance model. The simulation results in (Varvia et al, 2017) indicated improved estimation accuracy compared to the empirical vegetation index regression approach. Main advantages of the new method are that it also allows simultaneous estimation of other forest reflectance model parameters, such as leaf albedo, and produces uncertainty estimates for the model variables.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…The method is based on Bayesian inversion of a physically-based forest reflectance model. The simulation results in (Varvia et al, 2017) indicated improved estimation accuracy compared to the empirical vegetation index regression approach. Main advantages of the new method are that it also allows simultaneous estimation of other forest reflectance model parameters, such as leaf albedo, and produces uncertainty estimates for the model variables.…”
Section: Introductionmentioning
confidence: 94%
“…In this section, the Bayesian approach to LAI estimation is shortly summarized. Except for slight adjustments in certain hyperparameters, the methodology is identical to Varvia et al (2017) and the reader is referred there for more detail.…”
Section: Bayesian Estimation Of Effective Laimentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome such issues, applying Bayesian models to RTM inversion processes provides a straightforward way to quantify the covariance and uncertainty of parameter estimates while integrating different sources of information. RTM inversion has relied on the use of independent prior information to address the otherwise underdetermined challenge of estimating a high number of parameters from a limited number of observations [21], [24], [25]. As these studies neglect the parameter uncertainties or just approximate it, recent research has showed the efficiency of the hierarchical Bayesian technique called the Monte Carlo Markov Chain (MCMC) methods [26], [27].…”
Section: Introductionmentioning
confidence: 99%